Complete Readout of Two-Electron Spin States in a Double Quantum Dot - Martin Nurizzo; Baptiste Jadot; Pierre-André Mortemousque; Vivien Thiney; Emmanuel Chanrion; David Niegemann; Matthieu Dartiailh; Arne Ludwig; Andreas D. Wieck; Christopher Bäuerle; Matias Urdampilleta; Tristan Meunier (PRX Quantum, 2023)
We propose and demonstrate complete spin state readout of a two-electron system in a double quantum dot probed by an electrometer. The protocol is based on repetitive single-shot measurements using Pauli spin blockade and our ability to tune on fast timescales the detuning and the interdot tunnel coupling between the GHz and sub-Hz regime. A sequence of three distinct manipulations and measurements allows establishing if the spins are in S, T_{0}, T_{+}, or T_{−} state. This work points at a procedure to reduce the overhead for spin readout, an important challenge for scaling up spin-qubit platforms.